2015
DOI: 10.1128/cvi.00456-15
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Pneumococcal Surface Protein K of Nonencapsulated Streptococcus pneumoniae Provides Protection in a Mouse Model of Colonization

Abstract: e Current vaccinations are effective against encapsulated strains of Streptococcus pneumoniae, but they do not protect against nonencapsulated Streptococcus pneumoniae (NESp), which is increasing in colonization and incidence of pneumococcal disease. Vaccination with pneumococcal proteins has been assessed for its ability to protect against pneumococcal disease, but several of these proteins are not expressed by NESp. Pneumococcal surface protein K (PspK), an NESp virulence factor, has not been assessed for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Because nasopharyngeal colonization of pneumococcus is a prerequisite for pneumococcal infections and because PspK is critical for the nasopharyngeal colonization of NESp, the efficacy of PspK for developing pneumococcal vaccine has been investigated. 18 In this study, the authors found that i.n. immunization with recombinant PspK elicited good protection against nasopharyngeal colonization of not only NESp but the encapsulated strain in mice.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Because nasopharyngeal colonization of pneumococcus is a prerequisite for pneumococcal infections and because PspK is critical for the nasopharyngeal colonization of NESp, the efficacy of PspK for developing pneumococcal vaccine has been investigated. 18 In this study, the authors found that i.n. immunization with recombinant PspK elicited good protection against nasopharyngeal colonization of not only NESp but the encapsulated strain in mice.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, these strains have been shown to exhibit increased antibiotic resistance. [16][17][18][19] The prototype of PspK is a structurally well-characterized cell wall anchoring protein. Its N-terminal and Cterminal ends encode a conserved secretion signal motif and a LPxTG motif for secreting and anchoring on the peptidoglycan layer, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been almost no studies that have examined the mechanisms that allow NESp to persist and cause disease, the chinchilla has emerged as an effective model of OM caused by NESp ( 124 , 131 133 ). In this model, the replacement of the cps locus with pspK allowed efficient colonization in the NP along with increased virulence in the middle ear ( 31 , 132 , 134 ). Our study examined the ability of NESp to cause OM in the chinchilla along with the function of PspK during infection.…”
Section: Diseasementioning
confidence: 99%
“…Some non-encapsulated pneumococcal lineages express a surface protein, PspK, which is important in bacterial adherence to host epithelia as well as formation of biofilms and persistence in vivo. [16][17][18][19][20] PspK was also shown to increase virulence in encapsulated strains as well [21]. Non-encapsulated pneumococci have also been shown to persist within polymicrobial biofilms and cause OM in conjunction with NTHi [22].…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%